The Effect Of Breathing Exercise On Hypertension patients (Level II) Males of the Ages (45 – 50) Years Old - Abdul Sattar, Basil (Journal of Physical Education, 2014)
The evolution in human society left behind a negative impact on human health, especially the circulatory system and respiratory system, and in particular the case of(Hypertension) , which was taken into consideration researcher as one of the biggest health problems facing modern societies and this is what makes care a lot of health organizations in this serious problem and try to find appropriate solutions to them, using different drugs for treatment depending on the patient’s condition, and given what caused these medications and prescription drugs side effects went researchers to try to treat patients with high blood pressure without the use of medicines based on some natural methods , particularly the activities and exercises of various sports.